ZIC2 is downregulated and represses tumor growth via the regulation of STAT3 in breast cancer. Issue 2 (25th February 2020) - Liu, Zhi‐Hua; Chen, Mei‐Ling; Zhang, Qi; Zhang, Yu; An, Xin; Luo, Yi‐Ling; Liu, Xue‐Min; Liu, Shang‐Xin; Liu, Qian; Yang, Ting; Liu, Yan‐Min; Liu, Bin‐Liu; et al.
Abstract : Although early detection and systemic therapies have improved the diagnosis and clinical cure rate of breast cancer, breast cancer remains the most frequently occurring malignant cancer in women due to a lack of sufficiently effective treatments. Thus, to develop potential targeted therapies and thus benefit more patients, it is helpful to understand how cancer cells work. ZIC family members have been shown to play important roles in neural development and carcinogenesis. In our study, we found that ZIC2 is downregulated in breast cancer tissues at both the mRNA and protein levels. Low expression of ZIC2 was correlated with poor outcome in breast cancer patients and serves as an independent prognostic marker. Furthermore, overexpression of ZIC2 repressed, whereas knockdown of ZIC2 promoted, cell proliferation and colony formation ability in vitro and tumor growth in vivo . Using ChIP‐seq and RNA‐seq analysis, we screened and identified STAT3 as a potential target for ZIC2. ZIC2 bound to the STAT3 promoter and repressed the promoter activities of STAT3. ZIC2 knockdown induced the expression of STAT3, increasing the level of phosphorylated STAT3. These results suggest that ZIC2 regulates the transcription of STAT3 by directly binding to the STAT3 promoter. Additionally, interfering STAT3 with siRNAs or inhibitors abrogated the oncogenic effects induced by decreased ZIC2. Taken together, our results indicate that ZIC2 serves as a useful prognostic marker in breast cancer and acts as a tumor suppressor by regulating STAT3, implying that STAT3 inhibitors might provide an alternative treatment option for breast cancer patients with ZIC2 downregulation. Abstract : What's new? ZIC family members regulate neural development but have also been implicated in the development of various tumors. Here the authors report downregulation of ZIC2 in breast cancer cells. Low expression of ZIC2 correlated with poor outcome in breast cancer patients and served as an independent prognostic marker. The transcription factor STAT3 was identified as a potential target for ZIC2, and inhibition of STAT3 abrogated the oncogenic effects induced by decreased ZIC2 expression. STAT3 inhibitors might provide an alternative option for women with breast cancer showing ZIC2 downregulation.